2013
DOI: 10.1371/journal.pone.0068388
|View full text |Cite
|
Sign up to set email alerts
|

The Polyphenol Fisetin Protects Bone by Repressing NF-κB and MKP-1-Dependent Signaling Pathways in Osteoclasts

Abstract: Osteoporosis is a bone pathology leading to increase fractures risk and challenging quality of life. Since current treatments could exhibit deleterious side effects, the use of food compounds derived from plants represents a promising innovative alternative due to their potential therapeutic and preventive activities against human diseases. In this study, we investigated the ability of the polyphenol fisetin to counter osteoporosis and analyzed the cellular and molecular mechanisms involved. In vivo, fisetin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…It has shown synergistic activities with other anticancer agents (i.e. cisplatin and cyclophosphamide) in different carcinoma cell lines [2,3] and acts as an adjunct in cancer therapy to alleviate specific adverse effects related to cytotoxic agents or other therapeutics, including protection against ovariectomy-induced bone loss in mice [4] and has a renoprotective effect in cisplatininduced nephrotoxicity in rats [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has shown synergistic activities with other anticancer agents (i.e. cisplatin and cyclophosphamide) in different carcinoma cell lines [2,3] and acts as an adjunct in cancer therapy to alleviate specific adverse effects related to cytotoxic agents or other therapeutics, including protection against ovariectomy-induced bone loss in mice [4] and has a renoprotective effect in cisplatininduced nephrotoxicity in rats [5].…”
Section: Introductionmentioning
confidence: 99%
“…At present, fisetin has shown multiple biological activities including anti-proliferative (7,8), pro-apoptotic (9-13), neuroprotective (14) and anti-oxidative activities (15). Moreover, fisetin has been shown to suppress the proliferation of a wide variety of tumor cell, including prostate cancer (16), liver cancer (17), colon cancer (18) and leukemia (19) cells, and inhibit the mitogen-activated protein kinase (MAPK) and nuclear factor (NF)-κB signaling pathways in various type of cancer cell, such as colon and pancreatic cancer (14,(20)(21)(22)(23)(24). Fisetin was also reported to reduce the invasive and migratory capacity of the A549 human lung cancer cell line via the extracellular signal-regulated kinase (ERK) signaling pathway (25).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the JNK and p38 MAPK pathways contributes to pro-inflammatory cytokine production (153, 154). A recent study showed that in RAW264.7 macrophages, fisetin suppresses both p38 MAPK and JNK activation by increasing the levels of MAPK phosphatase-1 (MKP-1), an enzyme responsible for p38 MAPK and JNK dephosphorylation (155). Fisetin increases MKP-1 levels by a post-translational mechanism involving the inhibition of its ubiquitination and subsequent targeting to the proteasome (155).…”
Section: Mechanisms Of Action (Table 1)mentioning
confidence: 99%
“…A recent study showed that in RAW264.7 macrophages, fisetin suppresses both p38 MAPK and JNK activation by increasing the levels of MAPK phosphatase-1 (MKP-1), an enzyme responsible for p38 MAPK and JNK dephosphorylation (155). Fisetin increases MKP-1 levels by a post-translational mechanism involving the inhibition of its ubiquitination and subsequent targeting to the proteasome (155). Interestingly, it has been shown that ERK activation (see section 5.3) can promote MKP-1 stabilization via this pathway (155).…”
Section: Mechanisms Of Action (Table 1)mentioning
confidence: 99%
See 1 more Smart Citation